Design and Implementation of a WiFi Manager System on the ESP8266 Module for IoT Applications - Rahmatul Nisa; Eka Dodi Suryanto; Erwinsyah Sipahutar; Arie Budiansyah; Rudi Arif Candra (Global Advances in Science, Engineering & Technology (GASET), 2025)
The rapid growth of Internet of Things (IoT) technology has increased the demand for flexible and user-friendly wireless connectivity in embedded systems. One of the most widely used modules in IoT applications is the ESP8266, which integrates a microcontroller and WiFi capability in a compact and low-cost platform. Despite its advantages, WiFi configuration on the ESP8266 is commonly implemented using static credentials that are hardcoded into the firmware. This approach requires recompilation and reprogramming whenever network parameters change, making it inefficient and impractical for end users and large-scale deployment. This research proposes the design and implementation of a WiFi Manager system on the ESP8266 module to enable dynamic WiFi configuration without modifying the firmware. The proposed system allows the ESP8266 to automatically switch to Access Point (AP) mode when it fails to connect to a previously stored network. Users can then configure WiFi credentials through a web-based interface using a standard web browser. The configuration data are stored in non-volatile memory and used to reconnect the device in Station (STA) mode once a valid network is detected. The research methodology includes system design, firmware development using the Arduino platform, and functional testing to evaluate connectivity performance and reliability. Experimental results show that the WiFi Manager system successfully simplifies the WiFi configuration process, achieves a high connection success rate, and provides stable reconnection after power reset. The proposed approach enhances usability, deployment flexibility, and scalability of ESP8266-based IoT devices.